2022
DOI: 10.1111/1745-9125.12298
|View full text |Cite
|
Sign up to set email alerts
|

The American racial divide in fear of the police

Abstract: The mission of policing is "to protect and serve," but recent events suggest that many Americans, and especially Black Americans, do not feel protected from the police.Understanding police-related fear is important because it may impact civilians' health, daily lives, and policy attitudes. To examine the prevalence, sources, and consequences of both personal and altruistic fear of the police, we surveyed a nationwide sample (N = 1,150), which included comparable numbers of Black (N = 517) and White (N = 492) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 101 publications
3
65
0
Order By: Relevance
“…Compared to White Non-Hispanic respondents, respondents in all other racial groups were more likely to find the officers' actions inappropriate. This is further evidence of the suspicion and fear that these communities may have for police (see, Pickett et al, 2022). Simultaneously, respondents' perceptions of police procedural justice in their own communities were positively associated with greater perceived appropriateness of the use of deadly force depicted in the video.…”
Section: Body-worn Camera Footage and Hindsight Biasmentioning
confidence: 62%
“…Compared to White Non-Hispanic respondents, respondents in all other racial groups were more likely to find the officers' actions inappropriate. This is further evidence of the suspicion and fear that these communities may have for police (see, Pickett et al, 2022). Simultaneously, respondents' perceptions of police procedural justice in their own communities were positively associated with greater perceived appropriateness of the use of deadly force depicted in the video.…”
Section: Body-worn Camera Footage and Hindsight Biasmentioning
confidence: 62%
“…Though most police encounters with the public do not involve force, there is growing concern about unchecked police discretion and whether the police use their power in racially discriminatory ways (BBC News, 2020; "Public Perceptions of the Police," 2020). The concern is greatest among African-Americans (Gallup Inc, 2021;Pickett et al, 2021;Santhanam, 2020). This has led to what some have called a "crisis in policing" in which a significant part of US citizenry does not view the police as fair, trustworthy, or legitimate (Walker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Though most police encounters with the public do not involve force, there is growing concern about unchecked police discretion and whether the police use their power in racially discriminatory ways (BBC News, 2020; “Public Perceptions of the Police,” 2020). The concern is greatest among African-Americans (Gallup Inc, 2021; Pickett et al. , 2021; Santhanam, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they claim to operate under a neutral policy of “color blindness” (Welsh et al, 2020). As pointed out previously, the greater the frequency of stopping people of color, the more likely they are to be fearful rather than feeling safe (Pickett et al, 2021). As a result, experiences of use of force incidents are more likely, which manifests strategies and expertise in applying force.…”
Section: Fallacies About the Nature Of Biasesmentioning
confidence: 91%
“…For example, the lack of trust in the police in racial and minority groups may lead to different behaviors compared with citizens who trust the police. This has to be taken into account, given that recent data from the USA and Germany showed that, whereas white citizens generally feel safe around the police, people of color do not (Abdul-Rahman et al, 2020; Graham et al, 2020; Pickett et al, 2021). At this point, we want to emphasize that contextually irrelevant information biases humans in general, usually on an unconscious level without any awareness of the impact.…”
Section: Sources Of Cognitive Biases In Police Conflict Managementmentioning
confidence: 99%